1974
DOI: 10.1063/1.1655491
|View full text |Cite
|
Sign up to set email alerts
|

Tunable acousto-optic filter utilizing acoustic beam walkoff in crystal quartz

Abstract: A new configuration of a tunable acousto-optic filter utilizing acoustic beam walkoff in crystal quartz is described. By changing the acoustic frequency from 54 to 175 MHz, tuning of optical wavelength from about 650 to 250 nm is obtained in a single filter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…The AOTF of this geometry (Fig. 4) is characterized with an acoustic column walk-o like the collinear AOTF on α-SiO 2 [9]. Among the four discussed materials (Table), KYbW crystals can provide the best spectral resolution δλ ∼ 1/∆n because of the highest refractive index dierence ∆n = n p − n m .…”
Section: Collinear Ltermentioning
confidence: 99%
“…The AOTF of this geometry (Fig. 4) is characterized with an acoustic column walk-o like the collinear AOTF on α-SiO 2 [9]. Among the four discussed materials (Table), KYbW crystals can provide the best spectral resolution δλ ∼ 1/∆n because of the highest refractive index dierence ∆n = n p − n m .…”
Section: Collinear Ltermentioning
confidence: 99%
“…In this paper, the acousto-optic material paratellurite TeO 2 and calomel Hg 2 Cl 2 were chosen for the analysis. These materials are characterized by the pronounced elastic anisotropy so that the value of the acoustic phase velocity V strongly depends on a direction of propagation [3][4][5][6][7][8][9]. In particular, the slow-shear acoustic wave propagating in the XY plane at the angle θ = 45 • relatively to the axis X or Y possesses the extraordinary low phase velocity values V = 616 m/s, for paratellurite, and V = 347 m/s, for calomel.…”
Section: Introductionmentioning
confidence: 99%
“…The elastic waves propagating in the anisotropic crystals, such as paratellurite, and calomel are characterized by large walk-off angles ψ between the phase V and the group V g velocities of ultrasound [1][2][3][4][5][6][7][8][10][11][12][13][14][15]. It may be shown that the walk-off angle ψ between the acoustic wave vector K and the Poynting vector in these materials may exceed dozens of degrees, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations